Implementation of risk management in indonesia’s hospitality industry using OHS (occupational, health and safety) system - Joseph Aldo Irawan; Chondro Suryono; Emik Rahayu; Veronica Halim (Surya Hijau Manfaat, 2023)
In the industrial world, it is necessary to understand risk management to run a company well. Likewise, with the hospitality industry because there are many people in it. For some people, OHS is something other than essential and results in many workplace accidents. Research method used Relevant data is obtained with a qualitative descriptive method and assisted by documentation from many sources like internet, papers and case study. The goal of this research is to show the data of casualties and make the company realized the important of OHS management to prevent any casualties that may occurred In the future. By providing general training, companies can prevent work casualties. However, its implementation takes time because the workers are used to the old working method. OHS Training is an effort made by the company to be even better at maintaining the safety and security of the work environment. In the future, companies that provide OHS management will show zero casualties and good mental health of their workers because of the training and will effect to company good’s name.